2019
DOI: 10.17582/journal.pjz/20190527080541
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Diagnosis using Pregnancy-Associated Glycoproteins in the Serum of Pregnant Ruminants

Abstract: Authors' Contribution DK and HK designed the study. NA, MTT did statistical analysis. MT, MSK and RUK wrote the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Likewise, the sensitivity rate reported in the present study was higher than those from the previous findings [18,31,32]. The specificity of the PAG-EIA test for diagnosing non-pregnant cows obtained in the present study was higher than those reported, ranging from 66 to 90.7 %, in the researches assessing the effectiveness of the PAG-EIA test at [32][33][34][35]. Also, other investigations reported the specificity similar or slightly higher (91.1-97.2 %) carried out with the PAG-EIA test [18,29,31,36] and the PAG-RIA [15,27,29] in dairy cows in comparison to the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…Likewise, the sensitivity rate reported in the present study was higher than those from the previous findings [18,31,32]. The specificity of the PAG-EIA test for diagnosing non-pregnant cows obtained in the present study was higher than those reported, ranging from 66 to 90.7 %, in the researches assessing the effectiveness of the PAG-EIA test at [32][33][34][35]. Also, other investigations reported the specificity similar or slightly higher (91.1-97.2 %) carried out with the PAG-EIA test [18,29,31,36] and the PAG-RIA [15,27,29] in dairy cows in comparison to the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…However, none of these gene and protein markers have been validated by rigorous ROC curve analysis, nor have they been tested in actual production. Pregnancy-associated glycoprotein serves as a reliable protein biomarker to assess pregnancy in ewes, detectable as early as 30 days into gestation [49]; however, it is limited in species applicability, and its sensitivity may be skewed by pregnancy rate [50]. In brief, some previous studies still have certain limitations and shortcomings, and the discovery of new biomarkers in this study will provide a supplement for the diagnosis of early pregnancy in sheep.…”
Section: Discussionmentioning
confidence: 97%
“…Diagnosis of early pregnancy is an important tool in livestock species and has been performed traditionally via transrectal palpation or ultrasound. However, due to limitations in skilled technicians and their height, the demand for accurate pregnancy diagnosis has become increasingly important (Khan et al, 2020). Pregnancy diagnosis is an important part of successful reproductive management (Delhez et al, 2020) and early identification of non-pregnancy in female cattle.…”
Section: Discussionmentioning
confidence: 99%